Mechanical characterisation of the human dura mater, falx cerebri and superior sagittal sinus. (15th October 2021) - Walsh, Darragh R.; Ross, Aisling M.; Newport, David T.; Zhou, Zhou; Kearns, Jamie; Fearon, Conor; Lorigan, Jennifer; Mulvihill, John J.E.
Graphical abstract: Abstract: The cranial meninges have been shown to play a pivotal role in traumatic brain injury mechanopathology. However, while the mechanical response of the brain and its many subregions have been studied extensively, the meninges have conventionally been overlooked. This paper presents the first comparative mechanical analysis of human dura mater, falx cerebri and superior sagittal sinus tissues. Biaxial tensile analysis identified that these tissues are mechanically heterogeneous, in contrast to the assumption that the tissues are mechanically homogeneous which is typically employed in FE model design. A thickness of 0.91 ± 0.05 (standard error) mm for the falx cerebri was also identified. This data can aid in improving the biofidelity of the influential falx structure in FE models. Additionally, the use of a collagen hybridizing peptide on the superior sagittal sinus suggests this structure is particularly susceptible to the effects of circumferential stretch, which may have important implications for clinical treatment of dural venous sinus pathologies. Collectively, this research progresses understanding of meningeal mechanical and structural characteristics and may aid in elucidating the behaviour of these tissues in healthy and diseased conditions. Statement of significance: This study presents the first evaluation of human falx cerebri and superior sagittal sinus mechanical, geometrical and structural properties, along with a comparison to cranial dura mater. To mechanically characterise the tissues, biaxial tensile testing is conducted on the tissues. This analysis identifies, for the first time, mechanical stiffness differences between these tissues. Additionally, geometrical analysis identifies that there are thickness differences between the tissues. The evaluation of human meningeal tissues allows for direct implementation of the novel data to finite element head injury models to enable improved biofidelity of these influential structures in traumatic brain injury simulations. This work also identifies that the superior sagittal sinus may be easily damaged during clinical angioplasty procedures, which may inform the treatment of dural sinus pathologies.